From “Ulalume” to “Ulalume”: Pessoa Translating Poe - Defenu, Carlotta (TTR)

(untitled) (Association canadienne de traductologie, 2023)
One of the names that often emerges in Fernando Pessoa’s translation archive is that of the American poet Edgar Allan Poe. Pessoa attempted to translate at least 14 poems by Poe, and he also planned the publication of a Portuguese anthology of Poe’s “Main Poems” that never came to fruition. Among the documents related to the translation of Poe’s works in Pessoa’s archive, the translation of “Ulalume” is complemented by a rich genetic dossier comprising two autograph manuscripts and the marginalia extant in Pessoa’s copy of an anthology of Poe’s poetry. It provides a privileged glimpse into the different phases of the translation process and affords us the opportunity to unveil the strategies through which Pessoa was able to transpose not only the textual content of the source text, but also the complex phonetic and rhythmic references of the original poem into the Portuguese semantic universe.